STUDI TENTANG MITIGASI TINDAK KEKERASAN TERHADAP PEREMPUAN PADA DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA SAMARINDA - Ramadhani, Ria; Gunawan, Ketut; Budiman, Budiman (Jurnal Ilmu Pemerintahan, 2025)
The purpose of this study was to determine the prevention, handling, and recovery of violence against women at the Samarinda City Women's Empowerment and Child Protection Service (DP2PA). The research method used is descriptive qualitative. Data collection techniques used are observation, interviews, documentation. The data analysis technique used is Miles and Huberman in Sugiyono. The results of the study indicate that the Prevention of Violence Against Women by the Samarinda City DP2PA is carried out through direct and indirect socialization. Handling of Violence Against Women at the Samarinda City DP2PA begins with receiving reports through various channels with the aim of determining the needs of victims, including protection, legal assistance, or psychological assistance. Recovery of victims of violence against women by the Samarinda City DP2PA includes health and psychological services, in collaboration with health centers, hospitals, and the police to provide medical care and post-mortems, as well as psychological support.